Characterization of manganized soluble dietary fiber complexes from tigernut meal and study of the suppressive activity of digestive enzymes in vitro - Wang, Yifei; Wang, Weihao; Wu, Yunjiao; JiLiu, Junlan; Hu, Xin; Wei, Mingzhi; Cao, LongKui (Frontiers in Nutrition, 2023)
In this study, manganized soluble dietary fiber (SDF–Mn(II)) was prepared from tigernut meal using a microwave solid-phase synthesis method with SDF. Microscopic morphological and structural analyses of SDF–Mn(II) were carried out using scanning electron microscopy, Fourier infrared spectroscopy, UV full-band scanning, X-ray diffraction, a thermal analyzer, gel permeation chromatography, and nuclear magnetic resonance, and its in vitro hypoglycemic activity was initially investigated. The results of these analyses revealed that the reaction of Mn(II) with SDF mainly involved hydroxyl and carbonyl groups, with the Nuclear magnetic resonance (NMR) analysis showing that specific covalent binding was produced and substitution was mainly carried out at the C6 position. Moreover, compared with SDF, the SDF–Mn(II) complex exhibited a porous structure, red-shifted, and color-enhancing effects on the UV characteristic peaks, significantly increased crystallinity and decreased molecular weight, and improved thermal stability; in addition, SDF–Mn(II) afforded significantly enhanced inhibition of α-amylase and α-glucosidase and exhibited a good in vitro hypoglycemic activity.